2012
DOI: 10.18553/jmcp.2012.18.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Technology Assessment: Perspectives from Payers

Abstract: • The most important factors in formulary decision making have been reported to be safety, effectiveness, and efficacy, with FDA approval status, availability of alternatives, and acquisition cost of drugs also considered.• Spooner et al. (2007) ABSTRACTBAckground: Advancements in biologics and personalized medicine and the implementation of national prescription drug policies have likely prompted payers to implement additional health technology assessment and cost-containment strategies. A payer's decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
(10 reference statements)
1
26
0
Order By: Relevance
“…Nearly all participants indicated that RWE was useful for monitoring safety, conducting utilization management, and examining costs, but was less likely to be considered in P&T decision making, principally because of timeliness. This finding is supported by other studies that report payers relying heavily on RCTs for evaluation of comparative effectiveness [3,4]. In this study, however, similar to other studies, use of specific RWE studies was not based on common areas of agreement such as specific designs (e.g., prospective vs. retrospective studies), data sources (e.g., claims and EHRs), or tier of the journal in which the results are published, but rather whether the study answered relevant questions, transparently described the methods and results, and controlled for potential biases (e.g., design, funding, and authorship).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nearly all participants indicated that RWE was useful for monitoring safety, conducting utilization management, and examining costs, but was less likely to be considered in P&T decision making, principally because of timeliness. This finding is supported by other studies that report payers relying heavily on RCTs for evaluation of comparative effectiveness [3,4]. In this study, however, similar to other studies, use of specific RWE studies was not based on common areas of agreement such as specific designs (e.g., prospective vs. retrospective studies), data sources (e.g., claims and EHRs), or tier of the journal in which the results are published, but rather whether the study answered relevant questions, transparently described the methods and results, and controlled for potential biases (e.g., design, funding, and authorship).…”
Section: Discussionsupporting
confidence: 82%
“…A lack of understanding may lead decision makers to mistrust and place a lower importance on information from such studies, limiting their use in the decision-making process. Therefore, decision makers may instead over-rely on familiar sources of evidence, such as randomized controlled trials (RCTs), or use expert opinion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work has revealed inconsistencies in how US payers cover medical technology, for example [10][11][12]. Further research to elucidate coverage criteria would be helpful [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…1 The goal of CER-CI is to establish a consensus-based set of principles and tools to guide the design and evaluation of nonexperimental studies, including prospective and retrospective observational designs, so that the knowledge gained from these studies can be applied to improve patient health outcomes. 2 Health care reform has set the stage for this dialogue, and to best use the opportunity, participants need to understand how payers that assess pharmaceutical technology currently view observational study designs and which factors affect their credibility for this audience.…”
mentioning
confidence: 99%
“…1 This study used a stratified convenience sample with multiple recruitment methods. Although this method may reduce selection bias compared with recruiting from a single group such as AMCP members, the sample probably is still not representative of all U.S. payers, due to the use of professional relationships and research organization databases to recruit subjects.…”
mentioning
confidence: 99%